2023
DOI: 10.1039/d3fo00383c
|View full text |Cite
|
Sign up to set email alerts
|

A novel peptide derived fromHaematococcus pluvialisresidue exhibits anti-aging activity inCaenorhabditis elegans viathe insulin/IGF-1 signaling pathway

Wanshi He,
Junting Xie,
Zenghui Xia
et al.

Abstract: To explore the value of Haematococcus pluvialis (H. pluvialis) residues remaining after astaxanthin extraction and being discarded uneconomically, our previous study discovered the novel peptide (HPp) as a potential bioactive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
0
0
Order By: Relevance
“…Enzymatic hydrolysates of H. pluvialis residue protein was also reported to play antioxidant properties in vitro 26) . A recent study reported peptides derived from H. pluvialis residue displayed anti-aging activity in Caenorhabditis elegans 27) .…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic hydrolysates of H. pluvialis residue protein was also reported to play antioxidant properties in vitro 26) . A recent study reported peptides derived from H. pluvialis residue displayed anti-aging activity in Caenorhabditis elegans 27) .…”
Section: Discussionmentioning
confidence: 99%